2007
DOI: 10.1021/pr060502x
|View full text |Cite
|
Sign up to set email alerts
|

Dosage-Dependent Proteome Response of Shewanella oneidensis MR-1 to Acute Chromate Challenge

Abstract: Proteome alterations in the metal-reducing bacterium Shewanella oneidensis MR-1 in response to different acute dose challenges (0.3, 0.5, or 1 mM) of the toxic metal chromate [Cr(VI)] were characterized with multidimensional HPLC-MS/MS. Proteome measurements were performed and compared on both quadrupole ion traps as well as linear trapping quadrupole mass spectrometers. We have found that the implementation of multidimensional liquid chromatography on-line with the rapid scanning, high throughput linear trapp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
93
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(97 citation statements)
references
References 50 publications
1
93
3
Order By: Relevance
“…Digested peptides were separated on an in-house packed SCX (Luna)-C18 (Aqua) column and analyzed by an LTQ-Orbitrap (Thermo Fisher Scientific, San Jose, CA, USA) coupled to an Ultimate 3000 HPLC system (Dionex, Thermo Fisher Scientific Inc., Waltham, MA, USA). The raw spectra acquired by 12-step MS/MS runs were searched via SEQUEST v27 (Eng et al, 1994) against a custom pMMO database using parameters described elsewhere (Thompson et al, 2006;Sharma et al, 2012). Sequences of common contaminants such as trypsin and keratin were also concatenated to the database.…”
Section: Identification Of Pmmo In Metaproteomementioning
confidence: 99%
“…Digested peptides were separated on an in-house packed SCX (Luna)-C18 (Aqua) column and analyzed by an LTQ-Orbitrap (Thermo Fisher Scientific, San Jose, CA, USA) coupled to an Ultimate 3000 HPLC system (Dionex, Thermo Fisher Scientific Inc., Waltham, MA, USA). The raw spectra acquired by 12-step MS/MS runs were searched via SEQUEST v27 (Eng et al, 1994) against a custom pMMO database using parameters described elsewhere (Thompson et al, 2006;Sharma et al, 2012). Sequences of common contaminants such as trypsin and keratin were also concatenated to the database.…”
Section: Identification Of Pmmo In Metaproteomementioning
confidence: 99%
“…A DNA microarray targeting the whole genome of strain 195 was used to examine the transcriptome, while shotgun mass spectrometry-based proteomic analyses were used to query the proteome. Previous studies have demonstrated the utility of systems-level investigations for an understanding of the physiology of strain 195 (15, 17, 33) and other microbes (12,31,35,48,50,51). The identified differentially expressed genes are also of practical use as biomarkers for diagnosing nitrogenstressed conditions and directly assessing the physiology of Dehalococcoides (24) so that, together with geochemical measurements, they can be used to optimize contaminated-site conditions for success in bioremediation projects.…”
mentioning
confidence: 99%
“…The revolution in the use of gel-less online multidimensional LC-MS/MS technology for studying microbial isolates opened up a new regimen of comprehensive proteome characterization (4,8), now enabling the identification of a few thousand proteins from an individual cultivated microorganism (15,51,57,60). This permits a detailed, fairly deep glimpse into the molecular activities of the bacteria and now provides a robust technology which can be extended to environmental samples.…”
Section: Lc-ms-based Environmental Proteomicsmentioning
confidence: 99%